Contribution of Chromosome 14 to Exercise Capacity and Training Responses in Mice - Massett, Michael P.; Courtney, Sean M.; Kim, Seung Kyum; Avila, Joshua J. (Frontiers in Physiology, 2019)
Quantitative trait loci for exercise capacity and training-induced changes in exercise capacity were identified previously on mouse Chromosome 14. The aim of this study was to further investigate the role of Chromosome 14 in exercise capacity and responses to training in mice. Exercise phenotypes were measured in chromosome substitution strain mice carrying Chromosome 14 from the PWD/PhJ donor strain on the genetic background of a host C57BL/6J (B6) strain (B6.PWD14). Eight week old female and male mice from both strains completed a graded exercise test to exhaustion to assess intrinsic or baseline exercise capacity. A separate group of twelve-week old female and male mice, randomly assigned to sedentary control (SED) or exercise training (EX) groups, completed a graded exercise test before and after a four-week exercise training period. EX mice completed a 4-week training program consisting of treadmill running 5 days/week, 60 min/day at a final intensity of approximately 65% of maximum. For intrinsic exercise capacity, exercise time and work were significantly greater in female and male B6.PWD14 than sex-matched B6 mice. In the training study, female B6.PWD14 mice had higher pre-training exercise capacity than B6 mice. In contrast, there were no significant differences for pre-training exercise capacity between male B6 and B6.PWD14 mice. There were no significant strain differences for responses to training. These data demonstrate that PWD/PhJ alleles on Chromosome 14 significantly affect intrinsic exercise capacity. Furthermore, these results support continued efforts to identify candidate genes on Chromosome 14 underlying variation in exercise capacity.